Employee performance determinant analysis PT. Kahatex : The role of culture and organization leadership - Nabila, Athalla Talitha; Febrianti, Adjeng Mariana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Employee performance is one aspect that the company pays full attention to, because of its impact on the sustainability of the company itself. This study aims to see the influence of organizational culture and leadership style in the organization on the performance of employees of PT. Kahatex is located in Bandung Regency, West Java. This study uses a quantitative approach, with a sample of 70 employees. Researchers distributed questionnaires to employees to obtain primary data, and the data obtained were then processed using multiple regression analysis. This study indicate that organizational culture and leadership style variables have a significant positive effect on employee performance. The findings of this study can be a recommendation for leaders or managers to improve the performance of their employees. Companies need to pay attention to the culture that exists in the organization, as well as choose the appropriate leadership style, so that employee performance can increase.